Factors associated with problematic internet use among a large sample of Lebanese adolescents - Joseph E. Dib; Chadia Haddad; Hala Sacre; Marwan Akel; Pascale Salameh; Sahar Obeid; Souheil Hallit (BMC, 2021)
Abstract Background International literature clearly describes factors associated with problematic internet use, including substance dependence, online gambling, social impairment, and functional difficulties. Therefore, it was imperative to assess the extent to which young adolescents in Lebanese schools are affected by problematic internet use (PIU) and the factors associated with it. This large-scale Lebanese survey aims to evaluate the relationship between PIU, depression, and substance use, including alcohol consumption and nicotine use (cigarettes and waterpipe) among adolescents in Lebanese schools. Methods This cross-sectional study conducted between January and May 2019 assessed internet use through the Internet Addiction Test (IAT), with 'severe internet use' being the threshold for problematic internet use. It enrolled a total of 1810 adolescents aged 14 to 17 from 16 schools from all Lebanese Mohafazat. Results The majority of the participants had an average internet use 74.8% (95% Confidence Interval (CI): 0.72-0.76), 20.7% (95% CI: 0.18-0.22) had a frequent internet use, and 4.5% (95% CI: 0.03-0.05) had a severe internet use. Higher alcohol dependence (ß = 0.456, p < 0.001), higher depression (ß = 0.079, p = 0.001), and having separated parents vs. living together (ß = 0.136, p < 0.001) were significantly associated with higher IAT scores. Higher waterpipe dependence (ß = -0.218, p < 0.001) was significantly associated with lower IAT scores. Conclusion This study, the first and largest of its kind in the Middle East, showed that some psychiatric disorders, such as depression and substance use (smoking and alcohol), are associated with more problematic internet use among Lebanese adolescents. These results could serve as the first step for policymakers towards implementing early awareness campaigns to look at this problem more in-depth and come up with efficient actions to avoid it.